Anion Doping: A New Strategy for Developing High-Performance Perovskite-Type Cathode Materials of Solid Oxide Fuel Cells - Zhang, Z.; Zhu, Y.; Zhong, Y.; Zhou, W.; Shao, Zongping (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2017)
Overcoming the sluggish activity of cathode materials is critical to realizing the wide-spread application of intermediate-temperature solid oxide fuel cells. Herein, a new way is reported to tune the performance of perovskite-type materials as oxygen reduction electrodes by embedding anions (F−) in oxygen sites. The obtained perovskite oxyfluorides SrFeO3−σ−δFσ and SrFe0.9Ti0.1O3−σ−δFσ (σ = 0.05 and 0.10) show improved electrocatalytic activity compared to their parent oxides, achieving area specific resistance values of 0.875, 0.393, and 0.491 Ω cm2 for SrFeO3−δ, SrFeO2.95−δF0.05, and SrFeO2.90−δF0.10, respectively, at 600 °C in air. Such improved performance is a result of the improved bulk diffusion and surface exchange properties due to anion doping. Moreover, favorable stability in performance is also demonstrated for the F− anion-doped perovskites as oxygen reduction electrodes at 650 °C for a test period of ≈200 h. A combination of anion doping and cation doping may provide a highly attractive strategy for the future development of cathode materials.